The Application of Mentimeter to Improve Critical Thinking Skills in Al Islam dan Muhammadiyah (AIK) Course - Risdiani, Risdiani; Srifariyati, Srifariyati; Raharjo, Raharjo; Rohman, Abdul (Universitas Muhammadiyah Magelang, 2023)
Recent learning processes have not been fully student-cantered. The assessment tends to only giving score and ignores the skill of critical thinking. It requires changes in the use of learning strategies, methods, and media that activate students in the learning process in order to develop the skill of critical thinking. In this case, the use of Mentimeter can be an alternative. The objectives of the research is to find out the application of Mentimeter in the course of Al Islam and Muhammadiyah in the material of Ramadhan Fast, and to know how Mentimeter media can improve critical thinking skill of Nursing Department Students of Universitas Muhammadiyah Pekajangan Pekalongan that consist as 32 students of class A as experiment class and 34 students of class B as the control class. This study uses a quantitative research approach, specifically using a quasi-experimental method, the research design is pre-test, and the design of the control group is post-test. Based on the prerequisite test these two groups are not homogeneous and not normally distributed. From the results of research using the Mann Whiteney test, it is known that the Asymp. Sig. (2-tailed) of 0.00 0 which is less than 0.05. So, according to the basis for making a decision on the Mann Whitney U test, it can be concluded that Ho is rejected and Ha is accepted. This shows that there are significant differences in learning outcomes in the experimental class and the control class. The findings from this study indicate that Mentimeter media can effectively improve critical thinking skills.